Accumulation of polychlorinated dibenzo-p-dioxins, dibenzofurans, and biphenyls in livers of young sheep. (March 2015) - Hoogenboom, Ron L.A.P.; Stark, Marie Luise; Spolders, Markus; Zeilmaker, Marco J.; Traag, Wim A.; ten Dam, Guillaume; Schafft, Helmut A.
Graphical abstract: Highlights: Low intake of dioxins (PCDD/Fs) and PCBs results in high levels in livers. Higher chlorinated PCDD/Fs accumulate more than lower chlorinated congeners. PCB 126 accumulates more than less toxic congeners. A switch to clean feed leads to significant reduction of the liver levels. Abstract: A major part of sheep livers contains levels of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and polychlorinated biphenyls (PCBs) above the former but to some extent also the new maximum levels (MLs) in the EU. In order to investigate the relationship between the intake of these contaminants and their accumulation in livers, kidney fat and meat, young blackhead sheep were fed with grass pellets containing PCDD/Fs at 2.5 times the maximum level. Levels of PCDD/Fs in livers were already quite high at the start of the exposure but increased 3-fold within 56 d, exceeding the new product based MLs. Levels in meat and fat also increased but did not exceed the MLs. Although less elevated in the grass, both dl- and ndl-PCB levels also increased in liver and fat. Their kinetics in the tissues was less clear, potentially caused by increased levels in the straw given to the sheep during the whole experimental period. There was a clear difference in the behavior of the various congeners, the PCDFs and especially the higher chlorinated PCDFs and PCDDs showing a higher accumulation in the liver. In the case of the PCBs, this was particularly true for PCB 126. When switched to clean grass after 56 d, the levels in livers and other tissues decreased to about the levels in the control sheep within 56 d. This offers a potential solution for decreasing the intake of consumers.